Significance of preoperative butyrylcholinesterase level as an independent predictor of survival in patients with upper urinary tract urothelial carcinoma treated with nephroureterectomy. (21st November 2017) - Noro, Daisuke; Koie, Takuya; Hashimoto, Yasuhiro; Tanaka, Toshikazu; Ohyama, Chikara; Tobisawa, Yuki; Yoneyama, Tohru; Imai, Atsushi; Hatakeyama, Shingo; Yamamoto, Hayato; Kitayama, Masato; Hirota, Kazuyoshi
Abstract : This study validated preoperative butyrylcholinesterase as an independent prognostic factor for upper urinary tract urothelial carcinoma. Abstract: Objectives: Butyrylcholinesterase (BChE) is an alpha-glycoprotein synthesized in the liver. Its serum levels are reportedly correlated with disease activity in patients with cancer. The aim of this study was to estimate the potential prognostic significance of preoperative serum BChE levels in patients with upper urinary tract urothelial carcinoma (UTUC) undergoing radical nephroureterectomy (RNU). Methods: Of the 220 patients with UTUC who underwent RNU between 1995 and 2016 at Hirosaki University Hospital, 149 patients with available laboratory data were included for analysis. Covariates included age, sex, preoperative laboratory data, clinical T and N grades, tumor grade, tumor location and preoperative chemotherapy. Univariate and multivariate analyses were performed to identify clinical factors associated with overall survival (OS) and disease-free survival (DFS). Univariate analysis was performed using the Kaplan–Meier and log-rank methods, and the multivariate analysis was performed using a Cox proportional hazard model. Results: The median BChE level was 276 U/l and the optimal cut-off point for the serum BChE level was determined to be 218 IU/ml. The 5-year OS and DFS rates were 81.0% and 73.7%, respectively. The 5-year OS and DFS rates were significantly greater in the BChE ≥ 218 than <218 U/l groups (86.6% vs. 53.7%, P < 0.001 and 76.4% vs. 58.3%, P = 0.049, respectively). In multivariate analysis, BChE levels were most significantly associated with OS, whereas BChE level and tumor grade were significantly associated with DFS. Conclusions: This study validated preoperative serum BChE levels as an independent prognostic factor for UTUC after RNU.